Optimization of bromine-emerging etching compositions K₂Cr₂O₇-HBr-ethylene glycol for forming a polished surface of CdTe, ZnxCd₁-xTe and CdxHg₁-xTe - Chayka, M.V.; Tomashyk, Z.F.; Tomashyk, V.M.; Malanych, G.P.; Korchovyi, A.A. (Functional Materials, 2019)
The chemical dissolution of the CdTe single crystals and ZnxCd₁-xTe , ZnxCd₁-xTe solid solutions in aqueous solution of K₂Cr₂O₇-HBr-ethylene glycol in reproducible hydrodynamics conditions has been investigated for the first time. The graphic dependences &qout;etchant concentration - etching rate&qout; have been charted and determined the concentration limits of polishing etchant. It was demonstrated that the dissolution process of these materials is limited by the diffusion stages. The influence of the nature of the solid solutions of the ZnxCd₁-xTe and CdxHg₁-xTe on the rate and character of their chemical etching was established. The etchants composition and condition of realization of chemical-dynamic polishing process of these semiconductors were optimized.